Prevalence and Degree Trematoda Infection in Dairy Cattle Friesian Holstein at Koperasi Usaha Tani Ternak Suka Makmur Pasuruan - Rohmah, Miftahur; Sunarso, Agus; Hermadi, Herry Agoes; Hastutiek, Poedji; Permatasari, Dian Ayu; Kusnoto, Kusnoto (Journal of Parasite Science, 2024)
Trematode worm infections in dairy cattle have not been widely reported in various regions in Indonesia. This study aims to determine the prevalence and degree of trematode worm infection in Friesian Holstein dairy cattle at KUTT Suka Makmur, Pasuruan. The research design used survey study and cross-sectional study. The study was conducted in July-September 2023. The number of samples taken was 100, which were selected from proportional random sampling of four sub-districts, namely Grati, Nguling, Lekok, and Lumbang, with the age ranges under a year, 1-2 years, and above 2 years. The sample were examined using the sedimentation method and Flukenfinder® method. Positive samples were further examined using the McMaster method to determine the number of worm eggs per gram of feces. The results of this study obtained a prevalence of 54% with low and moderate degrees of infection. The trematode worm species found through fecal examination were Fasciola gigantica and Paramphistomum cervi. The results of chi square statistical analysis showed that sample examination method and age were related to the prevalence of trematode worms, yet location was not related to the prevalence of trematode worms. The results of kruskal wallis statistical analysis showed that age and location influence the degree of trematode worm infection.